Mechanisms of peripheral neuropathy associated with bortezomib and vincristine in patients with newly diagnosed multiple myeloma: a prospective analysis of data from the HOVON-65/GMMG-HD4 trial - Broyl, Annemiek; Corthals, Sophie L; Jongen, Joost LM; van der Holt, Bronno; Kuiper, Rowan; de Knegt, Yvonne; Duin, Mark van; Jarari, Laila el; Bertsch, Uta; Lokhorst, Henk M; Durie, Brian G; Goldschmidt, Hartmut; et al. (The lancet. Oncology, 2010)
Background - Bortezomib-induced peripheral neuropathy is a dose-limiting toxicity in patients with multiple myeloma, often requiring adjustment of treatment and affecting quality of life. We investigated the molecular profiles of early-onset (within one treatment cycle) versus late-onset (after two or three treatment cycles) bortezomib-induced peripheral neuropathy and compared them with those of vincristine-induced peripheral neuropathy during the induction phase of a prospective phase 3 trial. - Methods - In the induction phase of the HOVON-65/GMMG-HD4 trial, patients (aged 18-65 years) with newly diagnosed Salmon and Durie stage 2 or 3 multiple myeloma were randomly assigned to three cycles of bortezomib-based or vincristine-based induction treatment. We analysed the gene expression profiles and single-nucleotide polymorphisms (SNPs) of pretreatment samples of myeloma plasma cells and peripheral blood, respectively. This study is registered, number ISRCTN64455289. - Findings - We analysed gene expression profiles of myeloma plasma cells from 329 (39%) of 833 patients at diagnosis, and SNPs in DNA samples from 369 (44%) patients. Early-onset bortezomib-induced peripheral neuropathy was noted in 20 (8%) patients, and 63 (25%) developed the late-onset type. Early-onset and late-onset vincristine-induced peripheral neuropathy was noted in 11 (4%) and 17 (7%) patients, respectively. Significant genes in myeloma plasma cells from patients that were associated with early-onset bortezomib-induced peripheral neuropathy were the enzyme coding genes RHOBTB2 (upregulated by 1·59 times; p=4·5×10−5), involved in drug-induced apoptosis, CPT1C (1·44 times; p=2·9×10−7), involved in mitochondrial dysfunction, and SOX8 (1·68 times; p=4·28×10−13), involved in development of peripheral nervous system. Significant SNPs in the same patients included those located in the apoptosis gene caspase 9 (odds ratio [OR] 3·59, 95% CI 1·59-8·14; p=2·9×10−3), ALOX12 (3·50, 1·47-8·32; p=3·8×10−3), and IGF1R (0·22, 0·07-0·77; p=8·3×10−3). In late-onset bortezomib-induced peripheral neuropathy, the significant genes were SOD2 (upregulated by 1·18 times; p=9·6×10−3) and MYO5A (1·93 times; p=3·2×10−2), involved in development and function of the nervous system. Significant SNPs were noted in inflammatory genes MBL2 (OR 0·49, 95% CI 0·26-0·94; p=3·0×10−2) and PPARD (0·35, 0·15-0·83; p=9·1×10−3), and DNA repair genes ERCC4 (2·74, 1·56-4·84; p=1·0×10−3) and ERCC3 (1·26, 0·75-2·12; p=3·3×10−3). By contrast, early-onset vincristine-induced peripheral neuropathy was characterised by upregulation of genes involved in cell cycle and proliferation, including AURKA (3·31 times; p=1·04×10−2) and MKI67 (3·66 times; p=1·82×10−3), and the presence of SNPs in genes involved in these processes—eg, GLI1 (rs2228224 [0·13, 0·02-0·97, p=1·18×10−2] and rs2242578 [0·14, 0·02-1·12, p=3·00×10−2]). Late-onset vincristine-induced peripheral neuropathy was associated with the presence of SNPs in genes involved in absorption, distribution, metabolism, and excretion—eg, rs1413239 in DPYD (3·29, 1·47-7·37, 5·40×10−3) and rs3887412 in ABCC1 (3·36, 1·47-7·67, p=5·70×10−3). - Interpretation - Our results strongly suggest an interaction between myeloma-related factors and the patient's genetic background in the development of treatment-induced peripheral neuropathy, with different molecular pathways being implicated in bortezomib-induced and vincristine-induced peripheral neuropathy. - Funding - German Federal Ministry of Education and Research, Dutch Cancer Foundation Queen Wilhelmina, European Hematology Association, International Myeloma Foundation, Erasmus MC, and Janssen-Cilag Orthobiotech.